Assessing the Patients\' Hospitalization and Discharge Processes Based on Kaizen approach and Multiple-Criteria Decision Making (MCDM) in a Hospital - Sahba Sarvandi; Kambiz Shahroodi (Tehran University of Medical Sciences, 2016)
Background: Enhancing the need for health care services and its related costs, lead hospitals to improve and organize their processes. The aim of current study was to assess the Patientschr('39') Hospitalization and Discharge Processes Based on Kaizen approach and Multiple-Criteria Decision Making (MCDM) in an internal ward of one Hospital. Materials and Methods: In this descriptive analytical study, ten managers completed the hospitalization and discharge questionnaires and answered three open questions according to Kaizen principles. Then, satisfaction score was measured for 100 patients using a reliable questionnaire (α=0.93). At third phase, after evaluating the proposed solutions using Analytic Hierarchy Process (AHP), the managers prioritized them based on cost, time and effectiveness considering indicators. Results: Study findings revealed that mean scores of activity in hospitalization and discharge processes were 88.52 and 90.33 (out of 100) respectively, which showed high conformity with Kaizen approach. Also, mean scores of hospitalization and discharge satisfaction which indicated desirable satisfaction were 76.75 and 78.6 (out of 100), respectively. Based on managerschr('39') view points, results of MCDM and AHP methods indicated that effectiveness was the most important indicator and time as well as cost gained next priorities for solutions implementation. Conclusion: This study showed that although, hospitalization and discharge processes were relatively desirable in the internal ward in mentioned hospitals, it is still a necessary to seek the best solutions in terms of effectiveness, time and cost for patientschr('39') satisfaction.